Acceptance of new coconut seed Matag among coconut growers in Bagan Datoh, Perak and Bachok, Kelantan - Man, Norsida; Arif Shah, Jasmin (Human Resource Management Academic Research Society, 2020)
Cocos nucifera is cultivated as a plantation crop in more than 90 countries for numerous purposes. It is native to coastal areas of Malaysia, Indonesia, Philippines, etc. The coconut plant has the greatest number of purposes, particularly in the tropics. The demand for coconut is strong; however, a low supply is limited by fewer farmers cultivating the new hybrid seed of MATAG, thereby resulting in a short ability to fulfil the demand of the coconut industry. Therefore, this study was undertaken with the primary aim to evaluate the acceptance factor of new coconut seed MATAG among coconut growers. Other objectives include to identify the knowledge and attitude level of coconut growers towards the new seed MATAG and to clarify the perception level of the agricultural extension activities in technology transfer of the new seed MATAG. A total of 100 respondents, each from Kelantan and Perak, were involved in this study. A questionnaire that consists of five (5) sections was distributed to the coconut growers. Data obtained were subjected to descriptive and mean ranking analysis using Statistical Package for Social Science (SPSS) version 25. The study finds that the respondents perceived the new coconut seed favorably. Although the attitude and knowledge level among coconut growers toward the new coconut seed is high, the extension agencies must enhance their commitment to transfer the knowledge and information on the new seed. In line with this finding, the study highlights the importance of the extension agencies as the crucial liaison to approach the farmers and the Ministry of Agriculture and Food-based Industry (MAFI) should provide training, disseminate improved technologies and support extension officers to assist the smallholder farmers. The farmers should also cooperate with the extension agents and the agricultural extension agencies should, in turn, encourage the farmers to actively involved in the coconut production as well as helping them to resolve the issues at the farm that are impeding the production.